2015
DOI: 10.1080/09297049.2015.1049941
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training programs for childhood cancer patients and survivors: A critical review and future directions

Abstract: A robust literature has developed documenting neurocognitive late effects in survivors of leukemia and central nervous system (CNS) tumors, the most frequent cancer diagnoses of childhood. Patterns of late effects include deficits in attention and concentration, working memory, processing speed, and executive function, as well as other domains. As childhood cancer survivors are living longer, ameliorating deficits both in broad and specific neurocognitive domains has been increasingly recognized as an endeavor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 85 publications
1
21
0
Order By: Relevance
“…The present study showed that age at treatment, gender and time since diagnosis were not important factors associated with cognitive deficits. In previous studies, the rate of IQ decline was found to be associated with several factors, including younger age at time of treatment, longer time since diagnosis and female gender, as well as clinical variables such as hydrocephalus, use of radiotherapy and radiotherapy dose and the volume of the brain that received treatment (Mulhern, Merchant, Gajjar, Reddick, & Kun, ; Olson & Sands, ). These relationships were not demonstrated in the current study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study showed that age at treatment, gender and time since diagnosis were not important factors associated with cognitive deficits. In previous studies, the rate of IQ decline was found to be associated with several factors, including younger age at time of treatment, longer time since diagnosis and female gender, as well as clinical variables such as hydrocephalus, use of radiotherapy and radiotherapy dose and the volume of the brain that received treatment (Mulhern, Merchant, Gajjar, Reddick, & Kun, ; Olson & Sands, ). These relationships were not demonstrated in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…As survival rates continue to improve, it is important to understand how MB treatments affect survivors’ cognitive and psychological functioning and therefore, overall quality of life (Margelisch et al, ; Zeltzer et al, ). Children who receive treatments targeting the central nervous system, such as MB patients, are at an increased risk of developing cognitive late effects in comparison with survivors of other types of childhood cancer (Conklin et al, ; Olson & Sands, ; Palmer et al, ). Evidence indicates that age at treatment (i.e., younger), longer time since diagnosis, female gender, treatment intensity, type of chemotherapy (especially methotrexate), craniospinal irradiation, perioperative complications and possibly hydrocephalus, increase the risk of low cognitive functioning after treatment (Margelisch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly interventions to address negative sequelae are underway, but presently considered to be under developed (see for example a review of cognitive training programs Olson & Sands, 2015). Knowledge of the affected cognitive processes during treatment could inform interventions to prevent or manage changes and decrease the deleterious effects on school achievement and everyday function.…”
Section: Discussionmentioning
confidence: 99%
“…25 The negative impact of PBRT upon the Processing Speed Index, a critically important and broad skill that directly relates to one’s overall cognitive processing speed on a range of everyday tasks such as thinking, problem solving, reading, and writing, is consistent with the late effects of XRT and has been correlated with impairment in the growth of normal-appearing white matter. 2628 …”
mentioning
confidence: 82%